Moderate‐intensity treadmill exercise training decreases murine cardiomyocyte cross‐sectional area. Issue 5 (19th May 2015) - Sturgeon, Kathleen; Muthukumaran, Geetha; Ding, Dennis; Bajulaiye, Akinyemi; Ferrari, Victor; Libonati, Joseph R.
Abstract: The aim of this study was to examine the impact of moderate‐intensity treadmill exercise on the structure and function of the murine heart and its associated impact on Akt–AMPK–mTOR signaling. A secondary aim was to test whether the exercise phenotype was altered following a cardiotoxic bolus dose of doxorubicin (DOX). Two‐month‐old C57Bl/6J female mice remained sedentary (SED, n = 12) or were progressively trained with treadmill running for 2 months up to 18 m/min; 60 min/day, 5 days/weeks (EX, n = 11) or EX + DOX (15 mg/kg/dose) (EX + DOX, n = 6). Following treadmill training, mice underwent graded exercise tolerance testing and echocardiography. Training improved graded exercise tolerance by 68 ± 5% relative to SED, and this effect was not altered with bolus DOX. There were no changes in relative heart size with EX or EX + DOX versus SED. Regional posterior wall thickening was improved in EX and abrogated in EX + DOX. EX had a reduced cardiomyocyte cross‐sectional area (CSA) relative to SED, and CSA was further attenuated with DOX. Following EX, AMPK‐associated phosphorylation of ULK1(ser317) tended to be lower relative to SED. Akt‐associated phosphorylation of TSC2(thr1462) and mTOR(ser2448) were also decreased relative to SED. We observed an increase in AMPK activity with DOX that was not translated to downstream AMPK phosphorylation sites. We conclude that 2 months of moderate treadmill exercise training improves regional cardiac function and exercise capacity, but does not induce relative physiologic hypertrophy in female mice. Differential responses in Akt–AMPK–mTOR signaling may mediate the observed phenotype. Abstract : The aim of this study was to examine the impact of moderate intensity treadmill exercise on the structure and function of the murine heart and its associated impact on Akt‐AMPK‐mTOR signaling, as well as test whether the exercise phenotype was altered following a cardiotoxic bolus dose of doxorubicin (DOX). We conclude that 2 months of moderate treadmill exercise training improves regional cardiac function and exercise capacity, but does not induce relative physiologic hypertrophy in female mice. Differential responses in Akt‐AMPK‐mTOR signaling may mediate the observed phenotype.